Teaching and using of geographic categories of territory and landscape for graduation in countryside education in field of natural sciences and mathematics - Danilo Piccoli Neto; Sílvio Domingos Mendes da Silva (Universidade Federal de Santa Catarina, 2018)
The article aims to present the educational experiences and possibilities of using geographical categories (territory and landscape) for the undergraduate course in Natural Sciences and Mathematics of Countryside Education - UFSC. Two important points to be considered for the use of these categories are the specificity by forming area of the degree in Natural Sciences and Mathematics, which covers Physics, Biology and Chemistry and the context of education aimed at the education of and in the rural areas. The teaching of Geography in these terms involves the interdisciplinarity characteristic of Geography, which seeks to offer synergies between the mentioned disciplines and ways to teaching and correlation of contents and, in an extended perspective, offer subsidies for the future educator to understand contexts and understandings of reality, fundamental to the assumptions of Countryside Education